Selective Potentiation of Paclitaxel (Taxol)-Induced Cell Death by Mitogen-Activated Protein Kinase Kinase Inhibition in Human Cancer Cell Lines - McDaid, Hayley M. (2001)
Activation of the mitogen-activated protein kinase (MAPK) pathway in HeLa and Chinese hamster ovary cells after treatment with paclitaxel (Taxol) and other microtubule interacting agents has been investigated. Using a trans-reporting system, the phosphorylation of the nuclear transcription factors Elk-1 and c-jun was measured. Concentration- and time-dependent activation of the Elk-1 pathway, mediated primarily by the extracellular signal-regulated kinase (ERK) component of the MAPK family, was observed. Inactive drug analogs and other cytotoxic compounds that do not target microtubules failed to induce similar levels of activation, thereby indicating that an interaction between these drugs and the microtubule is essential for the activation of MAPKs. Evaluation of the endogenous levels of MAPK expression revealed cell-dependent expression of the ERK, c-jun N-terminal kinase, and p38 pathways. In the case of HeLa cells, time-dependent activation of ERK coincided with increased poly(ADP-ribose) polymerase (PARP) cleavage, phosphatidylserine externalization, and increased accumulation of cells in G(2)M. In both cell lines, inhibition of ERK activity potentiated paclitaxel-induced PARP cleavage and phosphatidylserine externalization, suggesting that ERK activity coincided with, but did not mediate, the cytotoxic effects of paclitaxel. We evaluated the nature of the interaction between paclitaxel and the MAPK kinase inhibitor U0126 in three cell lines, on the basis of a potential chemotherapeutic advantage of paclitaxel plus ERK inhibition. Our data confirmed additivity in those cells lines that undergo paclitaxel-induced ERK activation, and antagonism in cells with low ERK activity, suggesting that in tumors with high ERK activity, there may be an application for this strategy in therapy.